Confined Fe single atomic sites on (100) plane of anatase TiO2 nanofibers boost white LED driven Fenton-like norfloxacin degradation. (1st January 2023) - Ji, Zhilin; Cai, Rongsheng; Ye, Wanneng; Lu, Ping; Dong, Chung-Li; Huang, Yu-Cheng; She, Xilin; Butenko, Denys S.; Liu, Yiming; Zhu, Yukun; Yang, Dongjiang
Abstract: Developing efficient and sustainable photocatalyst is crucial for antibiotic degradation in water treatment. Iron (Fe) species modified semiconductor photocatalysts have been widely used in visible-light driven Fenton-like systems. However, the limited dispersion of Fe sites and low redox rate of the Fe(III)/Fe(II) restrict the catalytic performance. Herein, the atomic Fe sites with highly dispersed coordination centers were confined (100) facets exposed titania nanofibers (Fe-TNFs) for efficient photocatalytic Fenton-like norfloxacin (NOR) degradation. The optimized Fe-TNFs catalyst could achieve 95% NOR removal after 5 h of white LED illumination, which is 15% higher than that of nanostructured Fe species. The high performance is credited for the enhanced visible light absorption, and the efficient electron transfer through Fe–O bonds in Fe-TNFs enables the fast cyclic transformation of Fe(III)/Fe(II), which can promote the continuous production of OH in the photocatalytic Fenton-like system. This study can provide technical support for the developing a feasible and sustainable wastewater treatment solution, and provide reference for the fate and risk assessment of antibiotics in the environment. Highlights: Atomic Fe was confined on (100) exposed TiO2 by molten salt method. Single atomic Fe sites improve visible light absorption. Atomic Fe enhances the cyclic transformation of Fe(III)/Fe(II). Fe sites accelerate the formation of OH for efficient norfloxacin degradation.